Comparison of different methods of local anesthesia for platelet rich plasma injections to scalp in patients with hair loss - A prospective study - Vishnu Sundar Ramachandran; Singaravelu Viswanathan; Sivakumar, Krithiga (Asian Journal of Medical Sciences, 2024)
Background: Platelet-rich plasma injection (PRP) for hair loss is a widely accepted treatment modality at present. The most common problem with PRP is the pain that is associated with the procedure. The type of anesthesia is decided mostly based on preference rather than protocol. Aims and Objectives: The current study was undertaken to establish a standardized anesthetic protocol for PRP based on the response of the patients undergoing the treatment plan. Materials and Methods: The study included 60 patients who underwent four sittings of PRP at 1-month intervals for hair loss treatment. The modality of anesthesia was different during each of the sessions - topical anesthesia, vibration anesthesia, nerve block, and ring block. The order of anesthetic modality was different in each patient, to avoid bias. Responses by the patients for the following questions related to anesthetic pain during the procedure was recorded and analyzed based on the type of anesthetic procedure adopted. Results: Vibration anesthesia had the highest mean intra procedure numerical pain scale value. Nerve block was the least acceptable modality with maximal problems including the pain of the local anesthetic injection and the unsightly visible bulge in the supra orbital region. Post procedural pain was highest for vibration anesthesia and least for ring block. Highest acceptance was seen with the ring block technique. Conclusion: This is a preliminary study aimed at standardizing the anesthetic protocol for PRP. This modality of treatment involves multiple sittings with long total duration. Improving patient comfort with adequate anesthesia will improve compliance to a great extent.